Think tanks in Turkey in the era of JDP - V. A. Avatkov (MGIMO University Press, 2013)
After the collapse of the bipolar confrontation and in the era of globalization and regionalization of IR world and regional states face rising flows of information and extending mechanisms of foreign policy of different states. Turkey is not an exception. In this respect think tanks start playing a more significant role for its formulating of foreign policy.